Readiness and implications for adopting digitized payment of community health workers: a qualitative study of Benin and Uganda - Kabayambi, Joan P.; Bello, Kéfilath; Kisakye, Angela N.; Sekpon, Vanessa D.; Boyi-Hounsou, Christelle; Aweko, Juliet; Kiracho, Elizabeth Ekirapa; Waiswa, Peter; Padonou, Géraud; Okuonzi, Sam Agatre (Frontiers in Health Services, 2025)
IntroductionCommunity health workers (CHWs) provide lifesaving services to underserved and rural populations. However, CHWs face difficulties in receiving payment, which causes dissatisfaction and loss of motivation in their work. Digital health payments (DHPs) offer some solutions but there is a gap in knowledge and experiences in using DHPs in Africa. The study aimed to assess the countries' readiness to adopt DHP, and develop DHP adoption protocol and strategy.MethodsThis was a qualitative study based on a literature review, key informant interviews, in-depth interviews and a thematic analysis. Forty-nine interviews were carried out with participants consisting of CHWs, MNOs, managers/supervisors, and payers. A thematic analysis provided information on the readiness for DHP at individual, institutional and national levels. A protocol and strategy for adoption were imputed from the data.FindingsDirect literature on DHP was scanty. Instead, literature linked DHP to PHC, health financing, digital technology and digital economy. Respondents acknowledged the convenience of digital payment. CHWs observed the delay in digital payment, and the prolonged registration and processing. CHWs reported variations in payment and many cases of non-payment. All respondents expressed concern about the lack of systems for complaints. CHWs admitted that there was considerable digital illiteracy among them. Women appreciated their independence and privacy of financial dealings using DHP. No significant gender differences were reported in digital payment but significant differences were reported in literature. Readiness for DHP was rated high for DHP in both countries in organization, infrastructure and competences, but low in procedures and communication. Readiness in legislation, policy, digital infrastructure, and leadership, was rated medium in both countries. However, Benin showed a higher national-level readiness in political leadership and communication, while Uganda demonstrated higher levels of individual awareness, knowledge, and acceptance. To adopt and operationalize DHP in the two countries, the protocol identified essential inputs, processes, outputs, and outcomes, and cross-cutting elements of gender, leadership, policy and public awareness. Four broad strategies were imputed to support DHP: 1) promoting digitized PHC, 2) common national system for financing of CHWs, 3) integrated and interoperable systems, and 4) uniform payment of CHWs.ConclusionAlthough Benin and Uganda are at relatively different levels of readiness to adopt DHP, both countries reported similar experiences. Both countries have embraced DHP with positive policies, but major challenges remain in systems, digital knowledge and infrastructure. The two countries are transitioning to digital economy, which requires integration, interoperability and digitization of PHC and DHP. Common and harmonized systems for PHC financing need to be set up. As a major workforce in PHC, a deliberate effort is needed to improve CHWs motivation and performance through commensurate, safe and timely payments. Each country should design a manual to guide the adoption and operationalization of DHPs nationwide.